Value Priorities, Tenure and Organizational Citizenship - Tamayo, Álvaro (2012)
The objective of this research was to study the relationship between value priorities, tenure, and organizationalcitizenship. To our knowledge, personal value priorities have not been studied as antecedents of organizational behavior. Thesample was composed of 300 employees, men and women, with average age of 38.07 years. Two instruments were used: theSchwartz Value Inventory and the Organizational Citizenship Scale. Two groups of value priorities' subjects were considered:a high score group and a low score group. Three levels of organizational tenure were considered. The four second-order factorsof value priorities and the five organizational citizenship factors were considered for the analysis (Anova 2X3). Priorities ofself-transcendence, self-enhancement, collectivism and individualism values had a significant influence on several factors oforganizational citizenship. The impact of organizational tenure was limited to two factors: organizational climate and protectionof organizational patrimony